Causal relationships between dietary factors and spinal diseases: a univariable and multivariable Mendelian randomization study - Yi-Qi Chen; Yi-Qi Chen; Zhen-Ya Chen; Zhen-Ya Chen; Zheng-Qi Song; Zheng-Qi Song; Hai-Bo Liang; Hai-Bo Liang; Yi-Jun Li; Yi-Jun Li; Hong Su; Hong Su; et al. (Frontiers in Nutrition)
BackgroundSpinal diseases and their associated symptoms are prevalent across all age groups, and their incidence severely affects countless individuals’ quality of life. The role of daily habits in the progression of these diseases is increasingly emphasized in research. Moreover, there are reports suggesting associations between dietary factors and the onset of spinal diseases. However, the exact causal relationship between dietary factors and spinal diseases has not been fully elucidated.MethodsWe obtained GWAS data on 16 dietary intake and 187 dietary likings from the UK Biobank, and GWAS data on 23 types of spinal disorders from FinnGen R10. The analysis of causal effects was conducted using the Inverse Variance Weighted (IVW) test, and to ensure robustness, MR-Egger, Weighted median, and Bayesian weighted Mendelian randomization (BWMR) were utilized to validate the direction. Sensitivity analysis was conducted using the Cochran Q test and MR-Egger intercept test. Additionally, Multivariable MR (MVMR) was employed to examine the independent effect of alcohol intake frequency.ResultsIn summary, our study identified statistically significant causal associations between four dietary intake and 10 dietary linkings with various spinal disorders through univariable MR, with degenerative spinal changes showing the most significant dietary influence. Alcohol intake was identified as the primary risk factor, with other risk factors including poultry intake and likings for various types of meat. Protective factors mainly included intake and liking of fruits and vegetables. Additionally, various supplementary analytical methods along with heterogeneity and pleiotropy tests have confirmed the robustness of our results. To avoid the interference of diet-related diseases, multivariable MR analysis was conducted, showing that the incidence of cervical disc disorders may be influenced by gout, diabetes, and hypertension.ConclusionThis study indicates a potential causal relationship between dietary factors and the risk of spinal disorders, providing insights for the early detection and prevention. However, the specific pathogenic mechanisms require detailed basic and clinical research in the future.